Environmental problems indicator under environmental modeling toward sustainable development - P. Sutthichaimethee; W. Tanoamchard; P. Sawangwong; P Pachana; N. Witit-Anun (Global Journal of Environmental Science and Management, 2015)
This research aims to apply a model to the study and analysis of environmental and natural resource costs created in supply chains of goods and services produced in Thailand, and propose indicators for environmental problem management, caused by goods and services production, based on concepts of sustainable production and consumer behavior. The research showed that the highest environmental cost in terms of Natural Resource Materials was from pipelines and gas distribution, while the lowest was for farming coconuts. The highest environmental cost in terms of Energy and Transportation was for iron and steel. The highest environmental cost in the category of Fertilizer and Pesticides was for oil palm. For Sanitation Services, the highest environmental cost was movie theaters. Overall, the lowest environmental cost for all categories, except Natural Resource Materials, was for petroleum and refineries. Based on the cost index, coconut farming gained the highest Real Benefit to the farm owner, while pipelines and gas distribution had the lowest Real Benefit. If Thailand were to use a similar environmental problem indicator, it could be applied to formulate efficient policy and strategy for the country in three areas, namely social, economic, and environmental development.